Potential of Date-Seed/Snail Shells as a Carburizer for Enhanced Mechanical Properties of Mild-Steel - Kolawole M. Y.; Awoyemi E. A.; Abiona O. M. (Журнал інженерних наук)
The suitability of date-seed/snail shells as a carburizer for enhanced mechanical properties of mild-steel using the packed carburization technique was investigated in this work. Standard tensile, impact and hardness test samples prepared from mild-steel were subjected to pack-carburization process using mixtures of date-seed and snail shell in the ratio 60:40 respectively at 800, 900, and 1 000 °C for 3 hours. The carburized samples were quenched in water at room temperature and further tempered at 300 °C for 30 minutes for residual stress relief of the quenching effect. The mechanical properties and optical microstructure of carburized specimen were performed. Results indicated an enhanced mechanical property of the carburized mild-steel using date-steel/snail shell as a carburizer compared to un-carburized same steel material. The tensile strength and hardness increased with increasing carburizing temperature, though with an associated decrease in ductility. The peak hardness (32.82 HRB) and tensile strength (521 MPa) with equivalent 31.28 and 51.45 percentage increments respectively were obtained at carburizing temperature of 1 000 °C. Hence, using date-seed/snail shell powder as a carburizer can enhance the mechanical properties of mild-steel.